ANALISIS USER INTERFACE TERHADAP WEBSITE AKTA ONLINE BANYUWANGI MENGGUNAKAN METODE HEURISTIC EVALUATION - Siti Vika Ngainul Fitri; Oktalia Juwita; Tio Dharmawan (INFORMAL: Informatics Journal, 2019)
Banyuwangi Regency has a new innovation called " Lahir Procot Pulang Bawa Akta " which in this innovation is realized in the form of an Online Deed Website. Every information technology has an interface that can be a link between the user and the technology itself. Interface formation is influenced by needs, and information technology has different interface designs according to the needs of its users. The User Interface has the aim of making it easier for users to operate information technology that can make users feel comfortable using the application or technology. Heuristic Evaluation is one of the Usability evaluation methods that can be used to determine the extent to which a system is used by users to achieve certain goals with effectiveness, efficiency and satisfaction. This research is a research that is focused on the use of Heuristic Evaluation based on user interface design aspects of application usability through observation, interviews and questionnaires to users.